Late radiation toxicity after intraoperative radiotherapy (IORT) for breast cancer: results from the randomized phase III trial TARGIT A - Sperk, Elena; Welzel, Grit; Keller, Anke; Kraus-Tiefenbacher, Uta; Gerhardt, Axel; Sütterlin, Marc; Wenz, Frederik (Breast cancer research and treatment, 2012)
The randomized phase III trial TARGIT A showed non-inferiority regarding local control after intraoperative radiotherapy (IORT 20 Gy which was followed by whole breast radiotherapy (WBRT) in patients with risk factors only) in comparison to standard WBRT (50-56 Gy) after breast-conserving surgery in selected patients. This is the first analysis of long-term toxicities in the setting of TARGIT. Between 02/2002 and 12/2008, 305 patients were treated within TARGIT A (Arm A: n = 34 IORT, n = 20 IORT + WBRT for risk factors; Arm B WBRT: n = 55) or received IORT as a planned boost (control group: n = 196) at a single center. Toxicity was assessed according to the LENT SOMA scales. No significant differences were seen between Arm A and Arm B regarding fibrosis, breast edema, retraction, ulceration, lymphedema, hyperpigmentation, and pain. Arm A had significantly less telangiectases compared to Arm B (p = 0.049). In the subanalysis (Arm A IORT vs. Arm A IORT + WBRT vs. Arm B), fibrosis had a cumulative rate of 5.9 versus 37.5 versus 18.4 %, respectively (38.2 % IORT boost control group), at 3 years. No telangiectases were seen after IORT alone (0 % Arm A IORT vs. 17.5 % Arm A IORT + WBRT vs. 17.7 % Arm B). The hazard ratio of higher grade toxicity as first event was 0.46 (95 % CI, 0.26-0.83) for Arm A IORT as compared to Arm B (p = 0.010). No recurrences were seen after a median follow-up of 40 months (Arm A) and 42 months (Arm B). With its very low chronic skin toxicity rates and outstanding long-term results regarding toxicity and local control, IORT with 50 kV X-rays is a safe and effective method for treatment of selected breast cancer patients.